Land consolidation in mountain areas. Case study from southern Poland - Janus Jarosław; Łopacka Magdalena; John Ewa (Geodesy and Cartography, 2017)
Land consolidation procedures are an attempt to comprehensively change the existing spatial structure of land in rural areas. This treatment also brings many other social and economic benefi ts, contributing to the development of consolidated areas. Land consolidation in mountain areas differs in many respects from those implemented in areas with more favorable conditions for the functioning of agriculture. The unfavorable values of land fragmentation indices, terrain conditions and lower than the average soil quality affect both the dominant forms of agricultural activity and the limited opportunities to improve the distribution of plots in space, parameters of shape, and the area as a result of land consolidation. For this reason, the effectiveness of land consolidation in mountain areas can be achieved by improving the quality of transportation network and the accessibility of the plots, arranging ownership issues and improving the quality of cadastral documentation. This article presents the evaluation of the measures of effectiveness of land consolidation realized in mountain areas on the example of Łetownia Village in the Małopolska Province, located in the southern part of Poland. Selected village is an area with unfavorable conditions for the functioning of agriculture and high values of land fragmentation indices.